TEKNIK IDENTITY AND ACCESS MANAGEMENT PADA LAYANAN AMAZON WEB SERVICES - Dhimas Dirgantara; Is Mardianto (Faculty of Information Technology, Universitas Tarumanagara, 2019)
In this era, traditional technologies such as having servers and various kinds of hardware have been abandoned by large companies, which are turning to cloud computing technology. This technology makes it easier for companies to run their business. Of the many cloud computing service providers, Amazon Web Service (AWS) is one of the first and biggest service providers. Problems that occur in the use of cloud computing technology is the provision of access rights in data management. AWS has a service to manage access control for each service, namely Identity and Access Management (IAM). This service seeks to prevent activities that lead to security breaches. The results obtained are in the form of groups that can access AWS services according to the role given. Pada era ini, teknologi tradisional seperti memiliki server dan berbagai macam hardware telah ditinggalkan oleh perusahaan besar, yang beralih pada teknologi cloud computing. Teknologi ini memudahkan perusahaan dalam menjalankan bisnisnya. Dari banyaknya penyedia layanan cloud computing, Amazon Web Service (AWS) adalah salah satu penyedia layanan pertama dan yang terbesar. Masalah-masalah yang terjadi dalam penggunaan teknologi cloud computing adalah pemberian hak akses dalam melakukan manajemen data. AWS memiliki suatu layanan untuk mengatur kendali akses pada setiap layanan yaitu Identity and Access Management (IAM). Layanan ini berupaya mencegah aktivitas yang mengarah pada pelanggaran keamanan. Hasil yang didapatkan berupa group yang dapat mengakses layanan AWS sesuai dengan role yang diberikan.